DRABBL JANRI: AHAMIYATI VA GENEZISI (International journal of artificial intelligence, 2026)
This article explores the origins and causes of the "drabble" genre, which occupies a unique and significant place in modern Uzbek literature. It highlights its importance, distinctive features, as well as its connections to Uzbek and Oriental literature, along with its current standing in world literature. Furthermore, through the analysis of the work "Unlucky" by Alan Mayer, dedicated to the tragedy of Hiroshima and Nagasaki, the subtexts and unexpected endings (twists) characteristic of drabbles are examined. The article also provides insights into the role and influence of this compact genre on the lives of contemporary readers.